An Art Inquiry into the Experiences of a Family of a Child Living with a Chronic Pain Condition: A Case Study - Palmer, Kathryn; Shepard, Blythe (Canadian Journal of Counselling and Psychotherapy, 2008)
Chronic pain among children is poorly understood, and few studies portray the experiences of sufferers and their families. This qualitative case study aimed at gaining a rich description and a contextual understanding of the xperiences of a young chronic pain sufferer, aged 6, and her family members through an art-making process. Several examples of the art images are presented along with excerpts from the exploratory conversations that captured the meanings that the child and family members came to understand from the art-making process. A discussion focused on art as a research and counselling tool is presented.